Comparison of optical properties of TiO₂ thin films prepared by reactive magnetron sputtering and electron-beam evaporation techniques - Brus, V.V.; Kovalyuk, Z.D.; Parfenyuk, O.A.; Vakhnyak, N.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The envelope method was used to determine optical constants of TiO₂ thin films deposited by DC reactive magnetron sputtering and electron-beam evaporation techniques. The density and thickness of the thin films were calculated. Optical properties of the TiO₂ thin films were strongly dependent on the deposition technology. The TiO₂ thin films prepared by magnetron sputtering and electron-beam evaporation methods were established to be indirect band semiconductors with the band gap energies 3.15 and 3.43 eV, respectively.